BALANCING SUSTAINABILITY AND PROFITABILITY: OPTIMIZING INTELLECTUAL CAPITAL AND ITS CHALLENGES IN INDONESIAN MANUFACTURING COMPANIES - Julita, Julita; Iznillah, Muhammad; Andreas, Andreas (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2025)
Companies in Indonesia have faced challenges in balancing sustainability and profitability, with the optimization of intellectual capital emerging as a new perspective for creating competitive advantage. The research aims at examining the impact of Intellectual Capital and Corporate Sustainability Performance on Corporate Financial Performance. The secondary data was obtained from the sustainability and annual reports of manufacturing companies listed on the Indonesia Stock Exchange (2018–2020). Multiple regression analyses were conducted with SPSS 24. The results indicated that the environmental and social dimensions of sustainability performance significantly influenced financial performance, while intellectual capital and the economic dimension showed no significant impact. These findings highlighted the importance of managing sustainability and intellectual capital to achieve a balance between sustainability and profitability in the manufacturing sector. This research is limited by a small number of variables and a short observation period, requiring broader future research.